If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2x(x + 4) = 27 Reorder the terms: 7x + -2x(4 + x) = 27 7x + (4 * -2x + x * -2x) = 27 7x + (-8x + -2x2) = 27 Combine like terms: 7x + -8x = -1x -1x + -2x2 = 27 Solving -1x + -2x2 = 27 Solving for variable 'x'. Reorder the terms: -27 + -1x + -2x2 = 27 + -27 Combine like terms: 27 + -27 = 0 -27 + -1x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(27 + x + 2x2) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(27 + x + 2x2)' equal to zero and attempt to solve: Simplifying 27 + x + 2x2 = 0 Solving 27 + x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. 13.5 + 0.5x + x2 = 0 Move the constant term to the right: Add '-13.5' to each side of the equation. 13.5 + 0.5x + -13.5 + x2 = 0 + -13.5 Reorder the terms: 13.5 + -13.5 + 0.5x + x2 = 0 + -13.5 Combine like terms: 13.5 + -13.5 = 0.0 0.0 + 0.5x + x2 = 0 + -13.5 0.5x + x2 = 0 + -13.5 Combine like terms: 0 + -13.5 = -13.5 0.5x + x2 = -13.5 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. 0.5x + 0.25 + x2 = -13.5 + 0.25 Reorder the terms: 0.25 + 0.5x + x2 = -13.5 + 0.25 Combine like terms: -13.5 + 0.25 = -13.25 0.25 + 0.5x + x2 = -13.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = -13.25 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 63y^2-30=0 | | x^(1/3)=-1/2 | | 16x^4=(65x^2)-49 | | 5(25+8.50x)=5(20.75+9.75x) | | 9x-(x-5)=2x-(44+x) | | 17-3(1/10) | | 2(5x+4)+x+2= | | 9x-(x-5)=2x-(43+x) | | 10y-y+10y= | | 5(25+8.50x)=5(26.75+9.75x) | | 9x-(x-5)=2x-(40+x) | | 15.5-5(1/10) | | 9x-(x-5)=2x-(45+x) | | 2x-5=8x*7-x | | Y+56=148 | | 16x+2+7x= | | 9x-(x-5)=2x-(49+x) | | 76-53= | | 9x-(x-5)=2x-(39+x) | | 9x-(x-5)=2x-(29+x) | | 4x-2y=150 | | 71/2x41/3 | | 9x-(x-5)=2x-(23+x) | | 4x6/12 | | 3x+11=4x-4 | | 9x-(x-5)=2x-(6+x) | | 6y=712 | | -1-5+-3m= | | (2+3i)+(c+di)=2+i | | 14d^2=-27d | | (-12x+4x)+(6-12)= | | 5x-2x+x=9+3x+10 |